2022
DOI: 10.3390/cancers14102423
|View full text |Cite
|
Sign up to set email alerts
|

13C Natural Isotope Abundance in Urothelium as a New Marker in the Follow-Up of Patients with Bladder Cancer

Abstract: Bladder cancer (BC) is the most common urological malignancy and has a high incidence of recurrence. BC cells alter their nutrient uptake and metabolic pathways in order to continue the production of sufficient levels of ATP and metabolic intermediates for proliferation and survival. Changes in metabolic pathways regarding the rate of the enzymatic reaction and transport lead to differences in the content of natural isotopes (13C, 15N, 34S) between normal and cancerous tissues. The assessment of the stable iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the basis of the available literature, it can be assumed that changes in the isotopic content of nitrogen and carbon in tissue samples can be used to diagnose and monitor the progression of cancer [5][6][7]. For example, lower levels of 15 N in tumour tissue compared to healthy tissue can indicate decreased cellular protein synthesis in the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the available literature, it can be assumed that changes in the isotopic content of nitrogen and carbon in tissue samples can be used to diagnose and monitor the progression of cancer [5][6][7]. For example, lower levels of 15 N in tumour tissue compared to healthy tissue can indicate decreased cellular protein synthesis in the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…A study of bladder cancer patients revealed that differences in the abundance of 15 N and 13 C can be used as potential markers to predict the recurrence of the disease. It was demonstrated that 13 C depletion in normal urothelium in patients with surgically treated bladder cancer is associated with shorter disease-free survival [5].…”
Section: Introductionmentioning
confidence: 99%